Writing Postindustrial Places - Salvo, Michael J., author.
1 online resource
Keywords: Exploring the relationship between postindustrial writing and developments in energy production, manufacturing, and agriculture, Michael J. Salvo shows how technological and industrial innovation relies on communicative and organizational suppleness. Through representative case studies, Salvo demonstrates the ways in which technical communicators formulate opportunities that link resources with need. His book is a supple articulation of the opportunities and pitfalls that come with great change.